Osteochondritis dissecans of the medial femoral trochlear ridge in two bulldog siblings - Chico, A.; Marti, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Osteochondritis dissecans (OCD) of the medial femoral trochlear ridge was diagnosed in two seven months-old bulldog puppies. The disease was suspected radiographically and confirmed at exploratory arthrotomy. Both dogs showed a concurrent Grade I patellar luxation in the affected stifle. Treatment of the two conditions consisted of a recession wedge sulcoplasty and removal of a large cartilage flap. The outcome of the surgery, after a long-term follow-up (22 months) was excellent. To the authors’ knowledge, this is the first report of this type of OCD in the dog, its pathological findings and successful surgical treatment.
Keywords: OCD; dog; trochlear ridge